THE COMPLETENESS OF ENVIRONMENTAL LITERACY ASPECTS STUDIED IN THE ARTICLES PUBLISHED IN SEVERAL COUNTRIES - Ulfah, Mutia; Suyanto, Slamet; Aminatun, Tien (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Environmental literacy is indicated as one element of learning that is able to solve environmental problems. However, the extent to which the environmental literacy component is embedded in various levels of education has not been revealed much. This study aims to determine the environmental literacy of students in several countries, starting from primary school to university level. Research of the content analysis model was carried out by analyzing 25 articles from international journals and proceedings during 2012-2018. Environmental literacy instruments in this study refer to the evaluation of environmental literacy developed by Liang. The data analysis was performed quantitatively and presented as a percentage. The results showed that the majority of environmental literacy components that were widely studied and developed included cognitive, affective, and psychomotor (48%). Furthermore, junior high school (30.77%) and senior high school (23.08%) were chosen as research subjects in an effort to form a literate generation of the environment. The results of this study can be followed up with the optimization of efforts to strengthen environmental literacy through an appropriate learning process.